Large-scale Blended Learning Design in an Undergraduate Interprofessional Course in Norway: Students’ Perspectives from an Exploratory Study - Almendingen, Kari; Molin, Marianne; Šaltytė Benth, Jūratė (Journal of Research in Interprofessional Practice and Education)

(untitled) (Canadian Institute for Studies in Publishing Press (Simon Fraser University at Harbour Centre), 2021)
Background: The purpose of this study was to assess learning outcomes and student satisfaction after participating in a large-scale interprofessional (IPL) blended learning course.Methods and findings: In this cross-sectional study, students from health, social care, and teacher education programs completed two questionnaires. The majority were satisfied with the blended learning approach. The IPL group discussions resulted in learning outcomes that were two times higher than those from traditional instruction, including lectures and assignments. Health and social care students reported lower learning outcomes and satisfaction than teacher education and child welfare students (p < 0.05).Conclusions: The study demonstrated the feasibility of the blended learningapproach. However, IPL activities that are explicitly inclusive for all studentsshould be created for future courses.